Mast cells and innate immunity: master troupes of the avian immune system. Issue 3 (1st September 2017) - Rehman, Z.U.; Meng, C.; Umar, S.; Mahrose, K.M.; Ding, C.; Munir, M.
Abstract : Mast cells (MCs) are granulated cells of haematopoietic lineage and constitute a major sensory arm of the immune system. MCs dually guard hosts and regulate immune responses against invading pathogens. This property of the MCs is attributed to their adaptability to detect stress signals and pathogens, and the production of signal specific mediators to engage immune cells for clearance of infectious agents. Pathogen-specific signals establish basis for the initiation of adoptive immune responses. These immune regulatory roles of MCs have opened avenues to engage different MCs activators which culminate in effective passive immunisation. The molecular mechanisms and dynamics of functionalities of MCs in host defences have been extensively characterised in mammals and rodents, and research on MCs in avian species is emerging. This review surveys the development, morphology and distribution of MCs in different tissues of the poultry and highlight areas that can be exploited for disease control and prevention.